"Attractiveness" vs. "commonness" – the creation of heritage for the purpose of shaping tourist offer - Petrović Leš, Tihana (2010)
The presentation provides the results of the research carried out in Vinodol, Croatia during 2008 and 2009, which analysed cultural policy shaping and tourism project creation. The emphasis was thus placed on several topics: souvenir offer, annual customs, beliefs, cultural manifestations, traditional cuisine and architecture, while observing not isolated localities, but a wider cultural-historical region. The research attempted to encompass the perception and opinions of local people and those who devise the tourist offer and who are more actively involved in it. On one hand the research analysed the use of ethnographic elements within tourist offer in the period until the present moment, while on the other it recognised individual elements which had not been used so far. As significant cohesion and identification factors of the region we can point out local life stories or parts of family histories connected with male-dominant occupations until the 1970s. According to the data collected, a big number of Vinodol families throughout various generations counted with men employed in masonry and stone-masonry, who often migrated to other European countries and overseas, thus making a considerable impact on the life of the whole family. These stories were used as a background for the explanation of topics which we as researchers recognised as suitable for shaping the future tourist offer. Although they still strongly pervade individual, family and local histories, local people, but also cultural policy-makers, consider them ''too common'' and ''not sufficiently attractive'' to be incorporated into tourism. Therefore, this presentation will aim to question whether it is possible and how to represent ''everyday life'' in the context of tourism, or in order to create a ''tourist attraction'' it is essential to ''select'' individual, ''sufficiently attractive'', elements, for example, traditional handicrafts, food and architecture, commonly used when designing tourist amenities. In this context, the central issue is who participates in selecting these elements, attributes to them the function of heritage and thus legitimises them as suitable for incorporation into the tourist offer.